Carbon sequestration of mining waste in reducing carbon dioxide emission through mineral carbonation - Syed Hasan, Sharifah Nur Munirah (2020)
The process of extracting minerals from mining operation emits high carbon dioxide emission in the atmosphere. However, large quantities of waste materials produced from the mining operation can be utilized for carbon sequestration by mineral carbonation process. Therefore, this study was conducted to; (1) evaluate the potential characteristics of mining wastes such as gold, limestone and iron ore mine wastes for carbon sequestration; (2) enhance mineral carbonation process at varying particle size, temperature and pH in sequestering more carbon dioxide in carbonate form and; (3) develop potential application of mining wastes for long term carbon storage in brick production. Rock, soil, sludge and sediment samples were collected and analyzed for their characteristics including pH, particle-size distribution, mineralogical composition, morphological structure and chemical composition by integrating X-ray diffraction, scanning electron miscroscopy and energy dispersive X-ray analyses. The mineral carbonation experiment was conducted using mining waste at different particle size, temperature and pH. Brick production incorporating mining waste was produced at different mix design ratio and the effects of carbonation time and curing periods on carbon dioxide uptake were measured. Findings suggest that gold mine was identified as the source of MgO and Fe2O3 due to the presence of magnesium-iron silicate minerals; limestone mine as the source of CaO due to high availability of calcium-bearing mineral; and iron mine contains iron-calcium-magnesium silicate minerals as the source of Fe2O3, CaO and MgO that can be used as feedstock for mineral carbonation process. Iron mining waste was further evaluated for mineral carbonation due to variety of potential minerals and has the highest average divalent cation content. The effect of mineral carbonation using iron mining waste shows that smaller size particles (<38 μm) have achieved a higher calcium, iron and magnesium carbonation efficiency of 3.81%, 6.66% and 6.43%, respectively. As the temperature increased at 200°C, the maximum calcium, iron and magnesium carbonation efficiency of 4%, 5.82% and 5.62%, respectively were obtained. Increasing the pH at pH 12 resulted in greater calcium, iron and magnesium carbonation efficiency of 5.56%, 5.85% and 5.83%, respectively. Acceptable carbonation efficiency was achieved under the favorable conditions of ambient pressure. The incorporation of different types of mine waste indicates good durability of bricks, where limestone mine waste bricks have reduced water absorption and improved compressive strength of up to 0.52% and 40.23 N/mm2, respectively. Iron mine waste bricks show higher carbon dioxide uptake averaging 0.63%. Various mix design ratio and curing period are the most significant factors that affect the water absorption of carbonated brick specimens, while carbonation time had increased the compressive strength of brick specimens. Low carbon dioxide uptake can be improved by increasing the percentage of mining waste used up to 60% and lengthening the carbonation time up to 3 hours. Therefore, utilization of mining wastes as feedstock for mineral carbonation process can be regarded as a solution for waste minimization issue and seems to be an environmentally beneficial approach in reducing carbon dioxide emissions. This would be useful in promoting sustainable use of natural resources and for future mitigation strategies of mining-related issues.